Komparasi Penerapan Forward Selection Pada Algoritma C4.5 Dan Algoritma Naïve Bayes Untuk Memprediksi Kompetensi Karyawan (Studi Kasus: PT. XYZ) - Fuza Putra Arwanda; Hannie Hannie; Budi Arif Dermawan (Jurnal Ilmiah Wahana Pendidikan, 2021)
Monitoring and evaluation that is not well targeted towards employee assessment will cause problems in the development of human resources within a company. Currently the company PT. XYZ, is a new company which just started its production in 2020, thus monitoring and evaluation of the performance of each employee is very necessary. This study aims to compare C4.5 and the Naïve Bayes algorithm and add forward selection with the KDD (Knowledge Discovery in Database) methodology to predict competent and incompetent employees. Evaluation of the comparative use of the two algorithms, namely C4.5 and Naïve Bayes, was carried out by testing using Cross-Validation using 10-fold cross-validation.